Analisis Kepemimpinan Ekosistem: Studi Perbandingan Faktor Keberhasilan dan Kegagalan untuk Mewujudkan Organisasi Berkelanjutan - Andi Setyo Pambudi (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2026)
The phenomenon of leadership success and failure in managing cross-sectoral ecosystems has become increasingly prominent amid global complexity marked by interrelated economic, social, and environmental challenges. Although the concept of ecosystem leadership has garnered scholarly attention within organizational management discourse, a critical gap persists in understanding how specific leadership attributes contribute to either systemic sustainability or collapse. This study aims to analyze ecosystem leadership patterns across government and business sectors through an exploratory, cross-case comparative design. Data sources include academic publications, media narratives, policy documents, and public records of four prominent figures: Satya Nadella and Elizabeth Holmes from the business sector; Jacinda Ardern and Jair Bolsonaro from the governmental domain. Thematic and comparative analysis techniques were applied to identify key success and failure factors in ecosystem leadership. The findings reveal that collaboration, transparency, and adaptive governance structures are core determinants of effective ecosystem leadership, whereas narrative centralization and social exclusion are critical drivers of failure. The study recommends the development of a cross-sectoral leadership model rooted in sustainability principles, collaborative engagement, and public value orientation.